P233 ASSOCIATIONS BETWEEN LEFT AND RIGHT ATRIAL BIDIMENSIONAL STRAIN AND HEART FAILURE PROGRESSION. (18th May 2022) - Terazzi, E; Diomede, N; Correale, M; Di Terlizzi, V; Barone, R; Manuppelli, V; Brunetti, N; Iacoviello, M
Abstract: Background: Two dimensional speckle tracking is an innovative echocardiographic method which analyses myocardial deformation thus allowing the evaluation of both atrial and ventricular function. Recently, new software are available to measure it by semiautomatic analyses. Aim of the Study: To evaluate the association between left and right atrial Strain and the occurrence of clinical events related to the heart failure (HF) progression. Method. We enrolled 165 outpatients with chronic HF (76% males, NYHA 2.2 ± 0.69, ejection fraction 39±11%). All underwent a clinical and echocardiographic evaluation. An innovative software (TomTec, Philips) was used to analyse the images in order to semi–automatically calculate of atrial Strain. For each patient all the measures relative to the different phases of atrial deformation were considered both for the left atrium (LA) and the right one (RA), i.e. reservoir (r), conduit (cd) and contraction (ct). During the follow–up, we defined the HF progression as hospitalization due to HF worsening and/or heart transplantation and/or cardiovascular death. Results: During a median follow–up of 5 months, at least one event related to HF progression occurred in 22 patients: all underwent at least one hospitalization, 7 patients died because of cardiovascular reasons and 2 underwent heart transplantation. At Cox univariate analysis, LASr (HR: 0, 93; 95%CI: 0, 88–0, 97, p: 0.004; C–index 0, 7), LAScd (HR: 1, 09; 95%CI: 1, 01–1, 19; p: 0, 023; C–index: 0, 64), RASr (HR: 0, 95; 95%CI: 0, 90–0, 99; p: 0, 031; C–index: 0, 68), RAScd (HR: 1, 08; 95%CI: 1, 01–1, 15; p: 0, 021; C–index: 0, 67), but not LASct (HR: 1, 04; 95%CI: 0, 99–1, 09; p 0, 094; C–index 0, 62) and RASct (HR: 1, 02; 95%CI: 0, 96–1, 09; p: 0, 61; C–index: 0, 55), were significantly associated to HF progression. LASr and RASr showed the higher accuracy in predicting the events by the estimation of C index. At ROC curve analysis, for LASr the best cut–off was 16.1% (Sensitivity 83%, Specificity 56%) and for RASr 17.3% (Sensitivity 79%, Specificity 60%). Figure shows Kaplan–Meier curves for the considered end–point according with these cut–offs. Conclusions: The preliminary results of this study have showed the association between LA and RA Strain variables and the HF progression. The prosecution of this study will be finalised to demonstrate the prognostic independent and incremental significance.